2002
DOI: 10.1016/s0893-133x(02)00291-9
|View full text |Cite
|
Sign up to set email alerts
|

Aggression Escalated by Social Instigation or by Discontinuation of Reinforcement (“Frustration”) in Mice Inhibition by Anpirtoline: A 5-HT1B Receptor Agonist

Abstract: Experiments with social instigation or the omission of scheduled reinforcement show that serotonergic mechanisms may be involved in escalated aggression in animals. 5-HT 1B receptor agonists have anti-aggressive effects in individuals who show moderate as well as high levels of aggression. The present study compared the effects of the 5-HT 1B agonist anpirtoline (0.125-1.5 mg/kg) on (1) species-typical aggressive behavior in male mice, (2) aggression "instigated" or primed by prior exposure to the opponent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
106
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(110 citation statements)
references
References 65 publications
(99 reference statements)
3
106
1
Order By: Relevance
“…This finding implies that the level of aggression may have been heightened by the early weaning manipulation but we could not detect the attack bite behavior in isolation-induced aggression tests. One possible explanation for why the laboratory mice were not very aggressive in the isolation-induced aggression test was the fact that sexually naive mice were used in the previous study, and such mice have been reported to show low levels of aggression [2,15]. The purpose of the present study was to investigate the effects of early weaning on aggressive behavior exhibited in adulthood after the males were paired with females for 3 weeks.…”
mentioning
confidence: 93%
“…This finding implies that the level of aggression may have been heightened by the early weaning manipulation but we could not detect the attack bite behavior in isolation-induced aggression tests. One possible explanation for why the laboratory mice were not very aggressive in the isolation-induced aggression test was the fact that sexually naive mice were used in the previous study, and such mice have been reported to show low levels of aggression [2,15]. The purpose of the present study was to investigate the effects of early weaning on aggressive behavior exhibited in adulthood after the males were paired with females for 3 weeks.…”
mentioning
confidence: 93%
“…Both male and female mice that lack functional expression of the 5-HT 1B receptor gene (5-HT 1B Ϫ/Ϫ ) are more aggressive (Saudou et al, 1994;Bouwknecht et al, 2001), consistent with the anti-aggressive effect of several 5-HT 1B agonists including eltoprazine (Olivier et al, 1990), CP-94,253 (Fish et al, 1999;Chiavegatto et al, 2001), zolmitriptan , and anpirtoline (Rilke et al, 2001;Miczek and de Almeida, 2001;de Almeida and Miczek, 2002). Although agonists at 5-HT 1A receptors also decrease aggression in rodents (Olivier et al, 1995;Miczek et al, 1998), the mutant mice lacking 5-HT 1A receptors are more anxious, less reactive, and possibly less aggressive (Zhuang et al, 1999).…”
Section: Serotonin (5-ht) and Male Aggressionmentioning
confidence: 63%
“…CP-94,253, anpirtoline and zolmitriptan, all 5-HT 1B receptor agonists, when administered systemically have anti-aggressive effects under conditions that induce moderate or escalated levels of aggression such as social instigation, self-administration of alcohol or frustration, without impairing non-aggressive activities (2,3). This 5-HT receptor subtype received considerable attention when mutant 129/Sv mice lacking the gene for the 5-HT 1B receptor were found to display more aggressive behavior (4,5).…”
mentioning
confidence: 99%
“…Stimulation of 5-HT 1B receptors in the VO PFC proved to effectively reduce aggressive behavior in resident male mice confronting an intruder without discernible side effects (12). From a clinical perspective, it is important to study animal aggression that escalates above the species-typical level (2,3). One experimental approach used to escalate aggressive behavior is to provoke an animal by exposing it to a rival, and this procedure is often referred to as social instigation (17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation